A REVIEW OF MONTE CARLO METHODS AND THEIR APPLICATION IN MEDICAL PHYSICS FOR SIMULATING RADIATION TRANSPORT - Safarov Abror,; Mukhammedov Umidjon,; Ashurov Sindorjon, (TADQIQOTLAR.UZ, 2024)
Monte Carlo methods are used to calculate statistical behavior through the use of random number generators and probability density functions. They have been used extensively in medical physics for research in radiotherapy, designing technology, dosimetry, and advanced clinical applications. This paper provides a background on Monte Carlo methods and a review of radiation therapy physics and dosimetry. Additionally, there is a discussion of the different ways Monte Carlo methods are used in medical physics as well as a review of current research related to Monte Carlo methods. The final portion of this paper contains my own Monte Carlo simulation using the EGSnrc software toolkit to carry out two different simulations. One simulation serves as a basic introduction to using the software and demonstrates some of its capabilities, while the other is a more complex simulation that models a realistic scenario in medical physics.